Revisiting uses and gratification theory: a study on visitors to Annah Rais Homestay - Mus Chairil Samani,; Catohrinner Joyce Guri, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Uses and gratification theory has always been discussed within the functional paradigm where the media serve a specific purpose for any given audience. The perspective assumes that people know even before using the media why they are using it. It is argued in this article that the actual purpose of using mass media is never determined beforehand. Audience is made aware of the purpose after accidentally finding something of interest while using the traditional mass media. Serendity of information occurs after using the mass media. Thus, functionality is assumed rather than verified while using the various mass media. With the advent of the Internet, people shift through the various websites to obtain information relating to a specific purpose. To deduce functionality, a study was conducted on the uses and gratification of websites on homestays. A survey was carried out with 100 actual visitors to Annah Rais Homestays, Sarawak using a specially built questionnaire to collect data relating to perceive and actual uses, and perceive and actual gratification of information obtained from websites of three homestays’ service provider. The findings of the study conclusively found that the actual use of information after visiting a homestay is higher than the perceived use before visiting it. The actual gratification of information after visiting is higher than the perceived gratification before visiting it. Thus, the findings confirm the functionality of websites that could not have been proven in the various studies on traditional mass media.